Integración del corredor urbano de la carrera tercera con el Terminal de transporte terrestre de la ciudad de Ibagué (2022)
The objective of the present work is to integrate pedestrianly the Ibague´s transport terminal with the "Andrés López de Galarza" park, to develop the 3rd avenue´s urban, comercial and cultural corridor, favouring an ubran door for the city, due to the fact thar currently there are not inclusion elements. An inclusion will be generated by diferentes pedestrian elements, it will generate an inclusion to the 19th partial plan of urban renovation, that is currently aproved in order to unify the the "Andrés López de Galarza" park with the transport terminal; it is also suggested the reubication of 6 blocks to create a pedestrian, environmental, comercial and traffic inclusion to break the urban crack that produces negatives activities for the area and the people who arrives from the terminal. It is also thought in the implementation of diverses hotel areas, VIS and VIP houses and a bigger comercial zone, in order to this type of poblation take the park and produce an urban apropiation